Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2134/jnrlse.2002.0099
|View full text |Cite
|
Sign up to set email alerts
|

The Euphrates-Tigris Basin: A Case Study in Surface Water Conflict Resolution

Abstract: Historically, the Euphrates and Tigris waters have been a major source of freshwater conflict in the Middle East. Originating in Turkey, both rivers flow southwestward through Syria and Iraq, to discharge into the Persian Gulf. The irregularity in their seasonal flow necessitates the development of efficient storage and diversion systems to ensure adequate irrigation to the area's dominant agricultural sector. Consequently, water utilization projects undertaken by upstream riparian countries trigger confrontat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Turkey promised that it would not alter the Euphrates flow without informing Iraq, and, to adapt any future works to the needs of both states. In that treaty, Iraq was allowed to construct protection and observation posts in Turkey's territory to prevent downriver flooding (Fadel et al, 2002). First few hydrological projects began in Iraq in the 1950s where Samarra barrage and Dukan Derbendikhan dams were constructed in Iraq (Kibaroglu, 2008;Berardinucci, 2010).…”
Section: International Agreements a Historical Backgroundmentioning
confidence: 99%
“…Turkey promised that it would not alter the Euphrates flow without informing Iraq, and, to adapt any future works to the needs of both states. In that treaty, Iraq was allowed to construct protection and observation posts in Turkey's territory to prevent downriver flooding (Fadel et al, 2002). First few hydrological projects began in Iraq in the 1950s where Samarra barrage and Dukan Derbendikhan dams were constructed in Iraq (Kibaroglu, 2008;Berardinucci, 2010).…”
Section: International Agreements a Historical Backgroundmentioning
confidence: 99%
“…Turkey promised that it would not alter the Euphrates flow without informing Iraq, and, to adapt any future works to the needs of both states. In that treaty, Iraq was allowed to construct protection and observation posts in Turkey's territory to prevent downriver flooding [103].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…For example, a simpler version could be adapted for an Introduction to Natural Resources course that targets first‐year undergraduates. A simpler version could focus on water competition between upstream and downstream users, or could examine the effects of unsustainable land‐use upstream similar to Dovciak and Perry (2000) or El‐Fadel et al (2002). For higher‐level courses, we recommend using the full case as presented here, provided students are given ample time to truly explore all the angles of the case study.…”
Section: Teaching Notementioning
confidence: 99%
“…This case study was prepared to further students’ understanding of water management in a real‐life context and to encourage critical thinking about potential management solutions. Other examples of water‐related case studies can be found in Dovciak and Perry (2000), El Fadel et al (2002), and Brierley et al (2002). The case study presented here focuses on a watershed in Mexico where many common hot‐button water issues are highlighted.…”
mentioning
confidence: 99%